HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN KEBAHAGIAAN PADA MAHASISWA DALAM FORUM KOMUNIKASI PELAJAR MAHASISWA SUMATERA SELATAN (FKPMSS) DI SUMATERA BARAT - Muhammad Izha Afdwikki; DEVI LUSIRIA (CAUSALITA : Journal of Psychology, 2025)
This research aims to identify the relationship between social support and happiness in migrant students who are members of the South Sumatra Student Communication Forum (FKPMSS) in West Sumatra. The research uses a quantitative approach with a correlational design. Data was collected through questionnaires from 68 students who were research samples, using simple random sampling techniques. Data analysis was carried out using the correlations test to measure the strength of the relationship between the two variables. The research results show that there is a significant relationship between social support and happiness, where the relationship between the two variables is positive with moderate relationship strength (r = 0.593; p = 0.000). This shows that although the relationship between social support and happiness is not completely strong, other factors may be more dominant in influencing the happiness of overseas students.